2020
DOI: 10.1111/appy.12417
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of psychological distress and its association with coping strategies among medical interns in Malaysia: A national‐level cross‐sectional study

Abstract: Introduction: The prevalence of psychological distress is increasing worldwide.Stressful working environments and high expectations in medical practice put doctors at high risk of depression, anxiety, and stress, especially among medical interns.Effective coping strategies may reduce psychological distress in the clinical setting.This study aimed to determine the prevalence of psychological distress and its association with coping strategies among medical interns in Malaysia.Method: A total of 431 medical inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 51 publications
2
27
0
Order By: Relevance
“…The higher risk of depressive symptoms in female than in male students during the COVID-19 pandemic is in line with the findings of previous studies with samples of general university students (Li et al ., 2018 ; Gao et al ., 2020 b ; Ismail et al ., 2020 ). This phenomenon could be ascribed to the personality traits of females, such as higher levels of neuroticism/negative emotionality and conscientiousness, in comparison to males (Klein et al ., 2011 ; Weisberg et al ., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The higher risk of depressive symptoms in female than in male students during the COVID-19 pandemic is in line with the findings of previous studies with samples of general university students (Li et al ., 2018 ; Gao et al ., 2020 b ; Ismail et al ., 2020 ). This phenomenon could be ascribed to the personality traits of females, such as higher levels of neuroticism/negative emotionality and conscientiousness, in comparison to males (Klein et al ., 2011 ; Weisberg et al ., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies during COVID-19 have found positive reframing, humour and acceptance to be associated with better mental health, while self-distraction, self-blame and venting have been associated with poor mental health [ 41 ]. Others have found emotional and avoidance coping to be associated with stress, anxiety and depression [ 42 ] in addition to disengagement’s association with distress [ 43 ]. There has been a consistent correlation between burnout and dysfunctional coping among students [ 44 ] and educators [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emergency departments (ED) play a critical role in early identification of infected cases ( Bressan et al, 2020 ; National Health Commission of the People’s Republic of China , 2020 ), the provision of timely treatment and referral to other units/hospitals ( Lam et al, 2016 ; Lam et al, 2019 ). Due to highly stressful and overcrowding work environment, heavy workload, limited communication between multidisciplinary team members, inadequate knowledge of the epidemic, lack of personal protective equipment and guidelines on the diagnosis and treatment for patients in the early stage of the COVID-19 pandemic, ED clinicians were exposed to an elevated risk of infection, burnout, mental health problems and even workplace violence (WPV) ( Chapman & Styles, 2006 ; Gerberich et al, 2005 ; Ismail et al, 2020 ; Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%